Prognostic Value of Cardiac Troponin T After Myocardial Infarction: A Contemporary Community Experience - Gerber, Yariv (Mayo Foundation, 2012)
OBJECTIVE: To evaluate the role of cardiac troponin T (cTnT) in predicting death, recurrent ischemic events, and heart failure among community-dwelling persons with first myocardial infarction (MI). PATIENTS AND METHODS: Consecutive Olmsted County, Minnesota, residents with an incident MI between November 6, 2002, and December 31, 2007, were studied (N=1177; mean age, 68 years). Maximal cTnT value was measured at a median of 1 day after MI (median, 0.52 ng/mL; interquartile range, 0.16-1.75 ng/mL) and evaluated as a prognostic factor using measures of absolute risk. RESULTS: During a mean follow-up of 16 months, 276 deaths (23%) occurred, 341 patients (29%) experienced a recurrent ischemic event, and 326 patients (28%) experienced heart failure. A dose-response relationship was demonstrated early after MI between cTnT and the adjusted cumulative incidence of all outcomes. The multivariate-adjusted absolute risk differences (events per 100 patients) between the upper and lower cTnT tertiles at 30 days were 5.8 (95% confidence interval [CI], 1.4-10.2) for death, 5.2 (95% CI, 0.2-10.3) for recurrent ischemic event, and 6.9 (95% CI, 1.4-12.4) for heart failure. These differences were either maintained or increased at 2 years. CONCLUSION: In the community, cTnT level predicts death and nonfatal cardiac events independently of other prognostic factors. The increased risk associated with elevated cTnT level appears shortly after MI and persists for at least 2 years.